Humor, Sarcasm, and Gen Z Language Use in the Speech of the Guest Star Agak Laen on the Show Lapor Pak!: A Pragmatic Study - Renny Soelistiyowati; Mukhlas Ansori; Krishandini Krishandini (Universitas Pakuan, 2026)
The development of digital entertainment media has transformed communication patterns in society—particularly among the younger generation—through the use of humor, sarcasm, and various forms of popular language influenced by social media. This phenomenon is reflected in the comedy show Lapor Pak!, which features spontaneous interactions between the cast and guest stars, including the comedy group Agak Laen. This study aims to describe the humor strategies, forms of sarcasm, and Gen Z language usage in Lapor Pak! based on a pragmatic analysis. The study employs a qualitative descriptive method with a pragmatic approach. The data consists of utterances by the cast and Agak Laen guest stars, obtained from Lapor Pak! episodes on the Trans7 YouTube channel. Data was collected through observation and note-taking, then analyzed using pragmatic methods by identifying the context of speech, implicatures, violations of the principle of cooperation, and the forms of popular language that emerged. The results show that humor strategies are constructed through wordplay, roasting, irony, hyperbole, and violations of conversational maxims, which produce comedic effects. Sarcasm manifests as direct jabs, verbal taunts, and social criticism, serving to reinforce humor while shaping the dynamics of interaction among speakers. Furthermore, Gen Z language use is characterized by the utilization of digital slang, code-mixing, popular abbreviations, and contextual expressions that represent the communication culture of the younger generation. These findings indicate that the pragmatic strategies in Lapor Pak! not only play a role in creating humorous effects but also reflect the adaptation of language to contemporary digital culture and strengthen the communicative rapport between speakers and the audience. Keywords: Gen Z language, humor strategies, Lapor Pak!, pragmatics, sarcasm.